Parkinson's Disease and Sleep/Wake Disturbances - Todd J. Swick (Parkinson's Disease)
Parkinson's disease (PD) has traditionally been characterized by its cardinal motor symptoms of bradykinesia, rigidity, resting tremor, and postural instability. However, PD is increasingly being recognized as a multidimensional disease associated with myriad nonmotor symptoms including autonomic dysfunction, mood disorders, cognitive impairment, pain, gastrointestinal disturbance, impaired olfaction, psychosis, and sleep disorders. Sleep disturbances, which include sleep fragmentation, daytime somnolence, sleep-disordered breathing, restless legs syndrome (RLS), nightmares, and rapid eye movement (REM) sleep behavior disorder (RBD), are estimated to occur in 60% to 98% of patients with PD. For years nonmotor symptoms received little attention from clinicians and researchers, but now these symptoms are known to be significant predictors of morbidity in determining quality of life, costs of disease, and rates of institutionalization. A discussion of the clinical aspects, pathophysiology, evaluation techniques, and treatment options for the sleep disorders that are encountered with PD is presented.